HIGHHAYS, KILKENNY a medieval pottery production centre in south-east Ireland. - Devine, Emma; Drisceoil, Cóilín Ó (OXBOW BOOKS, 2022)
Comprehensive account of the 14th-century pottery-making site at Kilkenny, its output and impact.